2005
DOI: 10.1890/04-0934
|View full text |Cite
|
Sign up to set email alerts
|

Mosquito Habitats, Land Use, and Malaria Risk in Belize From Satellite Imagery

Abstract: Satellite imagery of northern Belize is used to examine the relationship between land use and habitats of the malaria vector, the Anopheles mosquito. A land cover classification based on multispectral Système Probatoire d'Observation de la Terra (SPOT) and multitemporal Radarsat images identified 11 land cover classes, including agricultural, forest, and marsh types. Two of the land cover types, Typha domingensis marsh and flooded forest, are habitats of immature Anopheles vestitipennis, and one, Eleocharis sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(61 citation statements)
references
References 28 publications
(57 reference statements)
1
60
0
Order By: Relevance
“…), see Fig. 3, with important consequences for the larval mosquito community (Pope et al 2005. Sparse macrophytes provide typical habitat for Anopheles albimanus larvae, whereas Typha spp.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…), see Fig. 3, with important consequences for the larval mosquito community (Pope et al 2005. Sparse macrophytes provide typical habitat for Anopheles albimanus larvae, whereas Typha spp.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…merging infections of humans and wildlife are often closely associated with anthropogenic alterations of the ecological and evolutionary relationships between hosts and pathogens, including climate change, biological invasions, land use change, and pollution (1)(2)(3)(4)(5). Owing to the complexity of pathogen-host-environment interactions, however, experimental evidence linking environmental change and increased infection is often lacking, leaving the ecosystem drivers of many emerging diseases unknown (5)(6)(7).…”
mentioning
confidence: 99%
“…A difference in the qualitative and quantitative mosquito compositions in different habitats is expected and noted in many papers (Rueda et al 2001;Cooper et al 2004;Pope et al 2005;Dale et al 2008). However, this study points out the relatively small number of species within the association of Genisto elataeQuercetum roboris caused by consecutive dry seasons, while previous research had shown a large number of species in this habitat (Merdić & Lovaković 1999) The Fuzzy c-means cluster analysis was used because of its reliability and the nature of the data, more specifically because of probability to classify each element to a cluster (Equihua 1990;Jain et al 1999).…”
Section: Discussionmentioning
confidence: 89%